2023
DOI: 10.1021/acsanm.3c02193
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Fe3O4 Nanocomposites from Layered Double Hydroxides as Catalysts for Selective Electroreduction of Carbon Dioxide

Abstract: The reduction of carbon dioxide to valuable chemical products is a hot topic of current research. In this article, Cu nanoparticle-decorated Fe 3 O 4 (Cu/Fe 3 O 4 ) is prepared by using layered double hydroxide (LDH) as the precursor. The CuFe-LDH is synthesized using the coprecipitation method and further reduced to obtain the final material Cu/Fe 3 O 4 . The uniform layered structure of LDH results in highly dispersed metallic elements in the corresponding Cu/Fe 3 O 4 , in which Cu atoms provide Cu 0 and Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
0
0
Order By: Relevance
“…Our group has previously demonstrated that CuFe-LDH could serve as an outstanding precursor for electrochemical catalysts due to its unique properties [47]. In this study, we successfully synthesized amorphous nitrided copper-iron oxides through the gas-phase nitridation of CuFe-LDH, exploiting the distinctive and highly dispersed metal components present in LDH.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously demonstrated that CuFe-LDH could serve as an outstanding precursor for electrochemical catalysts due to its unique properties [47]. In this study, we successfully synthesized amorphous nitrided copper-iron oxides through the gas-phase nitridation of CuFe-LDH, exploiting the distinctive and highly dispersed metal components present in LDH.…”
Section: Introductionmentioning
confidence: 99%